ANALISIS MODEL ALTMAN Z-SCORE DALAM MENGUKUR POTENSI KEBANGKRUTAN PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013 – 2017) - Herry Goenawan Soedarsa; Indrayenti Indrayenti; NM Oldy Apriyanto (Universitas Bandar Lampung (UBL), 2019)
This research is one of the references or tools for investors by using the Altman Z-Score model in knowing the financial condition of companies, especially consumer goods industry companies listed on the Indonesia Stock Exchange in 2013 - 2017. Based on the results of research conducted from 36 companies, it can be concluded that out of 36 companies only 20 companies or around 55.56% of the total sample companies that have good financial conditions from 2013 - 2017 because they have a Z-Score value of >2,99. While 16 other companies or around 44.44% of the total sample companies that have unstable financial conditions will even experience bankruptcy.